1985
DOI: 10.1016/s0022-5347(17)47669-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Stone Removal in Children

Abstract: Percutaneous removal of renal and ureteral calculi has become an established and successful procedure in adults. Stone disease in children often is metabolic or infectious in origin and multiple surgical procedures during a long interval may be required. Therefore, percutaneous stone removal could be particularly advantageous in these patients. We have performed percutaneous stone removal successfully in 7 children, none of whom required a second procedure or were discharged from the hospital with a nephrostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(90 citation statements)
references
References 5 publications
2
79
0
9
Order By: Relevance
“…They have been used both as monotherapy and combined as dual therapy [5,6]. The first paediatric PCNL series was reported in 1985 [7], and included seven children with a mean (range) age of 14 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years, treated using instruments for adults and with no significant complications. Since then much work has been done on paediatric urolithiasis, but few centres have reported their experience of PCNL in infants and very young children [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…They have been used both as monotherapy and combined as dual therapy [5,6]. The first paediatric PCNL series was reported in 1985 [7], and included seven children with a mean (range) age of 14 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years, treated using instruments for adults and with no significant complications. Since then much work has been done on paediatric urolithiasis, but few centres have reported their experience of PCNL in infants and very young children [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The first PNL operation was performed in 1985 (10) Table 1. PNL results in the age groups below and abovefor whom ESWL or RIRS is unsuccessful, PNL should be the first line of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10,[25][26][27][28][29][30] Firstly in 1985, Woodside et al [31] reported results of PNL procedures performed in pediatric patients. Success, and complication rates of PNL procedures resemble those in the adult patients.…”
Section: Discussionmentioning
confidence: 99%